The interplay between online consumer reviews and firms' interventions from three actors' perspectives - Millanyani, Heppy (2021)
The World Tourism Organisation reports that 90 per cent of consumers read online consumer reviews before making a purchase decision, with 83 per cent admitting that the reviews influence them. Adding to the knowledge that reviews are a significant source of information in tourist decision making due to a high level of perceived trust compared to advertising, sheds some light on the importance of online reviews on the decision-making process. Online reviews are the manifestation of customer engagement behaviour, which contains customers’ assessment of the company’s service quality, as a result of their comparison between their expectation of the service and the actual service quality received. Therefore, they can also be used by companies as a source of information about the market. Acknowledging the importance of online consumer reviews for consumers’ decision-making processes, many companies have decided to become more active by responding to reviews. Some research suggests that this initiative has successfully enabled companies to gain a competitive advantage by nurturing customer engagement behaviour and enhancing consumer perception of service quality. Companies’ engagement with reviews can also be used as an avenue for service recovery. However, contrasting results suggest that negative effects can occur because consumers feel disturbed and see the response as a defensive mechanism from the company. Whilst there is much literature on the views of tourists on reviews and companies’ responses, there is hardly any addressing the perspectives of the firms being reviewed. This represents an important omission, since they are key actors, contributing communication into the online review platform. Further, additional research should also be conducted to acknowledge the interaction between both positive and negative influence on consumers behaviour. The existing literature mainly concludes that reviews and responses have positive or negative effects, which do not represent the real situation faced by all actors in the environment. The current thesis addresses these by conducting qualitative research, which is also lacking in the literature. Taking the view that meaning is socially constructed, and multiple realities exist, the thesis explores the perspectives of three groups of participants using a qualitative approach with semi-structured interviews as the data collection method. The researcher conducted 31 interviews with reviewers, 21 interviews with potential guests and 12 interviews with hotel firms. After applying thematic analysis as suggested by Braun & Clarke (2006), the thesis concludes that online consumer reviews and hospitality firms’ responses have yielded five paradoxes in an online environment. These paradoxes are caused by the effects arising from the interaction between consumer reviews and hospitality firms’ responses, as experienced by the three actors. This thesis contributes to the theory on reviews as an information source and search processes by highlighting the paradoxes caused by the positive and negative impacts of online reviews and hospitality firms’ responses simultaneously. The thesis also contributes to the theory about the ways reviews and responses are understood and evaluated by highlighting the links to self-concept theory for the first time. Furthermore, the thesis contributes to theories of service quality gaps by revising the service quality model from Parasuraman, Zeithaml and Berry (1985). This thesis also contributes to theories of motivation in online engagement activity in word-of-mouth and the theory on the impact of hospitality firms’ responses on consumers. Finally, the thesis contributes to the theory about the ways responses to reviews should be created by emphasising the benefits of including para-social interaction in the response, providing some practical suggestions for hospitality firms and marketers in general.